Recent Publications (Quarterly Journal of Economics, 1947)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 61, Issue 3, May 1947, Pages 500–502, https://doi.org/10.1093/qje/61.3.500 Published: 01 May 1947